Copyright In The Digitization Of Library Collections: A Case Study Of The Library Stikes Wira Medika Bali - I Gusti Agung Lintang Saraswati Rahadi; Sri Rohyanti Zulaikha; Cut Afrina (AL Maktabah, 2026)
The digitization of library collections presents significant challenges related to copyright, particularly in balancing public access to information with legal protection for creators. This study aims to analyze the implementation of copyright in the digitization of collections at the Library STIKES Wira Medika Bali, identify the obstacles encountered, and formulate appropriate management strategies. The method used is qualitative research with a descriptive approach. Data were collected through in-depth interviews, observations, and documentation, then analyzed using an interactive model (data reduction, data presentation, and drawing conclusions). The results of the study indicate that the library’s digitization policy has integrated legal, administrative, and technical aspects, including verification of work ownership, the use of author statements, and a multi-tiered access system. However, implementation still faces challenges such as the complexity of copyright regulations, limitations in digital system integration, a shortage of human resources, and the absence of standardized technical guidelines. The strategies implemented include access restrictions, strengthening legal documentation, user education through information ethics outreach and plagiarism checks, and collection selection based on academic needs. This study concludes that responsible collection digitization requires a comprehensive and sustainable approach, including strengthening integrated systems, developing operational standards, enhancing librarian capacity, and collaborating with external parties. Thus, libraries can serve as mediators that maintain a balance between information access and legal compliance in the digital age. Keywords: Copyright, Digital Rights Management (DRM), Library Digitization